O uso do termo Mercosul no discurso diplomático do 1º Governo Dilma Rousseff (2011-2014) como meio para a inserção internacional do Brasil - Bezerra, Vinicius Araújo (2016)
Mercosur, in the course of its history, went through moments of elation and concern. During the euphoria, the regional block could provide to the members with na increase in trade flow and insert their economic more competitively in the contexto of globalization. During concern, the partners used to protectionism to address the crisis and generated suspicions in relation to Block due, in particular, the relationship between Brazil and Argentina. From the late 1990s, both decided to revitalize Mercosur in order to enlarge it economic scope for political, cultural and social. Mercosur must therefore be understood as a process in constant improvement. Brazilian diplomacy in this context established a strategic relationship with Argentina to realize that if there is no agreement between them, the Brazilian project for regional integration would not advance. Brazil encouraged the creation of the South American space with Mercosur as the core of this policy. To this end, it sought to build a regional identity as a way of encouraging political consultation between the states, cooperation and development, but without neglecting the guiding principles of Brazilian foreign policy: autonomy and universalism. From the idea of concentric circles, Brazil signed with Argentina, Mercosur placed in the core with links to other regional bodies with the pragmatic goal of international integration. By analyzing the speeches by the president, Dilma Rousseff, in his first term, the intention that Mercosur remains an instrument for Brazil to achieve part of its international demands. Thus, from the paradigm of the PEB, the conceptions of the constructivist theory of International Relations and discourse analysis methodology the dissertation proposes, at the end, to understand to what extent the Brazilian intention in Mercosur serves to achieve its international goals.